Revitalizing the Roles and Relevance of Traditional Morality of Sidaama People of Ethiopia in Sustaining Peace: The Case of "Halaale" Principle - Barako, Basha Bekele (International Journal of Humanities, Management and Social Science (IJ-HuMaSS), 2023)
It is widely accepted that employing armed forces will successfully accomplish the objective of maintaining peace. However, these solutions are not always effective in bringing lasting peace. In order for peace to become deeply ingrained in societal lives, it is frequently necessary to look deeply into the social and moral foundations of a society. This particular study was designed to investigate the functions and applicability of conventional moral values and practices in upholding peace. Specifically, the paper was intended to study the practical and potential benefits of Sidaama moral ideals and principles for maintaining peace focusing on Halaale principle. To achieve this objective several key informants were interviewed as primary data sources besides a compressive literature review on the matters of peace maintenance, conflict resolution, ethics and moral principles and practices of Sidaama people. Accordingly, the analysis was made on the data collected from the informants and contents of the references. Finally, it was found that “Halaale” principle of Sidaama People has both a preventative role in conflicts and maintaining harmony by binding the members of the community to the communitarian good. Based on this, it was recommended that, the diligent attention should be paid both at policy and society levels to make use of the fruits of traditional moral principles rather than lessening them as obsolescent practices.